BIMBINGAN BAGI ANAK YANG BERKEBUTUHAN KHUSUS (AUTISME) DI KELAS 1 SEKOLAH DASAR GMIT 03 KALABAHI - Ester Prity Claudia Biri; Matias Lau Mau Pating, Uriana Mabileti, Norciana Well, Yessy Mata, Petrus Mau Tellu Dony, Antonius A (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
This study aims to guide children with special needs, specifically those with developmental disorders or disabilities. This study focused on children with autism spectrum disorders at GMIT 03 Kalabahi Elementary School, specifically in class L. The method used in this study was a qualitative approach using observation, interviews, and documentation techniques. The results indicate that there is a boy who has had autism since birth, characterized by difficulties in communication and social interaction. The guidance provided focuses on strengthening social interactions and developing simple communication skills with consistency and empathy. This study emphasizes the importance of the involvement of teachers, parents, and the school environment in supporting the child’s development. This research is expected to form the basis for developing effective guidance strategies for children with special needs in elementary schools.